2023
DOI: 10.1101/2023.02.07.527406
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neutralization of SARS-CoV-2 BQ.1.1 and XBB.1.5 by Breakthrough Infection Sera from Previous and Current Waves in China

Abstract: SARS-CoV-2 is continuing to evolve and diversify, with an array of various Omicron sub-lineages, including BA.5, BA.2.75, BN.1, BF.7, BQ.1, BQ.1.1, XBB and XBB.1.5, now circulating globally at recent time. In this study, we evaluated the neutralization sensitivity of a comprehensive panel of Omicron subvariants to sera from different clinical cohorts, including individuals who received homologous or heterologous booster vaccinations, vaccinated people who had Delta or BA.2 breakthrough infection in previous wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 57 publications
3
17
0
Order By: Relevance
“…Consistent with our previous findings 14 , individuals who received a three-dose vaccination series demonstrated detectable geometric mean titers (GMTs) of neutralizing antibodies against the WT virus, but the GMTs for B.1.351, B.1.617.2, BA.1 and BA.2 showed significant reductions compared to WT, while the neutralizing titers against the BA.5, BF.7, BQ.1.1, CH.1.1, and XBB.1.5 were reduced to nearly undetectable levels. In individuals who experienced breakthrough infections with the BA.5 or BF.7 variants, high levels of neutralizing titers were observed against variants that preceded BA.5 and BF.7, with GMTs consistently exceeding 1000.…”
Section: Neutralization Of Sars-cov-2 Main Sub-lineages Prior To Xbb1...supporting
confidence: 94%
See 1 more Smart Citation
“…Consistent with our previous findings 14 , individuals who received a three-dose vaccination series demonstrated detectable geometric mean titers (GMTs) of neutralizing antibodies against the WT virus, but the GMTs for B.1.351, B.1.617.2, BA.1 and BA.2 showed significant reductions compared to WT, while the neutralizing titers against the BA.5, BF.7, BQ.1.1, CH.1.1, and XBB.1.5 were reduced to nearly undetectable levels. In individuals who experienced breakthrough infections with the BA.5 or BF.7 variants, high levels of neutralizing titers were observed against variants that preceded BA.5 and BF.7, with GMTs consistently exceeding 1000.…”
Section: Neutralization Of Sars-cov-2 Main Sub-lineages Prior To Xbb1...supporting
confidence: 94%
“…The approved vaccines including those utilizing the whole virus as well as those based on specific viral components, such as the protein subunit vaccines and mRNA vaccines 10 . Our previous research [11][12][13][14] , along with findings from other investigators 15,16 , indicated that both primary and booster vaccinations from approved vaccines exhibited reduced efficacy against the Omicron variant and its sub-lineages, particularly over an extended period.…”
Section: Introductionmentioning
confidence: 85%
“…Our data from individuals who had received three doses of an ancestral spike-based vaccine indicated that antibodies against the two variants, BA. presented by other groups using both pseudovirus (PSV) and authentic virus assays against panels of vaccinated (three-and four-dose) with additional break-through infection in a globally diverse population [53][54][55][56][57][58][59][60]. It is also of interest that the GM titres are comparable despite the genetic diversity in the variants tested against our four-dose panels.…”
Section: Discussionmentioning
confidence: 99%
“…to neutralisation by panels of triple vaccinated volunteers in other studies as well as in those with breakthrough infections with BA.1 and BA.2[51,52].In the UK, as boosters containing bivalent antigens were deployed in the Autumn of 2022, we continued our assessment of emerging variants with samples from individuals who had received a BA.1/ancestral booster. The majority also had at least one breakthrough infection between February 2021 and December 2022 (Alpha to XBB.1.5).…”
mentioning
confidence: 99%
“…3 The only agent authorized by the FDA for use as SARS-CoV-2 preexposure prophylaxis (PrEP), 4 tixagevimab plus cilgavimab (Evusheld), is not effective against the Omicron variant. 5,6 Therefore, the Omicron and its subvariants remains a significant health threat, and it is desirable to develop agents that can provide protection against the variants and reduce related disease burden.…”
Section: Introductionmentioning
confidence: 99%